2013
DOI: 10.7860/jcdr/2013/4917.3038
|View full text |Cite
|
Sign up to set email alerts
|

The Antibiotic Susceptibility Patterns of Uropathogenic Escherichia Coli , With Special Reference to the Fluoroquinolones

Abstract: Context: The emergence of drug resistance to trimethoprimsulfamethoxazole, the penicillins, cephalosporins, and fluoroquinolones by Uropathogenic Escherichia coli (UPEC) has limited the options for selecting the appropriate antibiotic for the treatment of urinary tract infections. Aims:The The E. coli isolates, which were obtained from the culture of urine samples,were studied for their antibiotic resistance patterns, with special reference to the antimicrobial activity of the fluoroquinolones and the producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
26
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 6 publications
8
26
1
1
Order By: Relevance
“…Guajardo-Lara et al, in a study performed in Mexico, found 24.7% of resistance to ciprofloxacin (15) . Similar resistance percentage (23.5%) was also reported in India (26) .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Guajardo-Lara et al, in a study performed in Mexico, found 24.7% of resistance to ciprofloxacin (15) . Similar resistance percentage (23.5%) was also reported in India (26) .…”
Section: Discussionsupporting
confidence: 75%
“…An Indian study (26) showed E. coli prevalence of 48.3%; other studies showed prevalence of 71.3% in Turkey (1) and 77.5% in Belgium (3) . In the literature, data on other pathogens prevalence show large variation, while in this study, the most prevalent uropathogens, excepting E. coli, were S. saprophyticus (9.4%) and Proteus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli is a facultative Gram-negative bacterium, which can cause many infections, like diarrhea, urinary tract infections, meningitis, peritonitis, and septicemia in humans (13). However, the most prevalent form of the extraintestinal infection caused by E. coli is urinary tract infection (14).…”
Section: Discussionmentioning
confidence: 99%
“…It will help in directing the proper and the prudent utilization of antibiotics. The formulation of an appropriate institutional and organizational antibiotics policy will go a long way in controlling these infections (Shariff et al, 2013).…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Broad range of antibiotics resistance encoding genes from microorganisms have been found in wastewater effluents, surface water, river water, groundwater and drinking water (Dolejska et al, 2011). Multi-drug resistance has been shown in E. coli (Shariff et al, 2013).…”
mentioning
confidence: 99%